A Fault Signal Processing Method Based on An Improved Prony Algorithm - Yang, Nan; Lu, Yanming; Zhang, Jianmei; Zhang, Zhenzhen; Ding, Li; Yang, Cong; Dong, Zhengqiang; Liu, Songkai; Xiong, Wei; Zhu, Binxin; Zhang, Lei; Huang, Yuehua; et al. (Frontiers in Energy Research, 2022)
The fault of power systems introduces a severe challenge in terms of fault recording analysis, and the traditional Prony method cannot perform satisfactorily in the process of signal recordings fitting caused by faults. Therefore, an improved adaptive Prony algorithm is proposed in this article to study the characteristics of fault recordings. Specifically, the search step size is taken as an adaptive variable, and the mean square relative fitting error (MSRFE) is set as the criterion. Then, a large step is employed to rapidly determine an approximate segmentation point in the initial stage of the searching process, and its horizon is gradually reduced to establish an accurate subsegment point. Finally, the Prony algorithm is deployed to analyze the subsegment fitting original signal. The proposed approach has been simulated on an assumed fault signal, and the results validate the accuracy and efficiency of the method.